2017
DOI: 10.7448/ias.20.1.21848
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning young adults from paediatric to adult care and the HIV care continuum in Atlanta, Georgia, USA: a retrospective cohort study

Abstract: Introduction: The transition from paediatric to adult HIV care is a particularly high‐risk time for disengagement among young adults; however, empirical data are lacking.Methods: We reviewed medical records of 72 youth seen in both the paediatric and the adult clinics of the Grady Infectious Disease Program in Atlanta, Georgia, USA, from 2004 to 2014. We abstracted clinical data on linkage, retention and virologic suppression from the last two years in the paediatric clinic through the first two years in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 21 publications
3
44
0
1
Order By: Relevance
“…Nevertheless, a study conducted at Zomba Central Hospital in Malawi showed that the odds of attrition were 3.7-times lower in ALHIV exposed to Teen Clubs than those who were not exposed [17]. This was consistent with studies conducted in high income countries [10,12,19,20] South Africa [18]. However, the Malawian and South African studies did not explore the clinical outcomes of these adolescents and did not identify the speci c elements of the teen clubs which were critical in ensuring successful transitioning.…”
Section: Introductionsupporting
confidence: 75%
“…Nevertheless, a study conducted at Zomba Central Hospital in Malawi showed that the odds of attrition were 3.7-times lower in ALHIV exposed to Teen Clubs than those who were not exposed [17]. This was consistent with studies conducted in high income countries [10,12,19,20] South Africa [18]. However, the Malawian and South African studies did not explore the clinical outcomes of these adolescents and did not identify the speci c elements of the teen clubs which were critical in ensuring successful transitioning.…”
Section: Introductionsupporting
confidence: 75%
“…IeDEA-SA Steering Group: Frank Tanser, Africa Centre for Health and Population Studies, University of Kwazulu-Natal, Somkhele, South Africa; Christopher Hoffmann, Aurum Institute for Health Research, Johannesburg, South Africa; Michael Vinikoor, Centre for Infectious Disease Research in Zambia, Lusaka, Table 5. Regression of predictors of retention in the 12 months after the age of transition across transition-age thresholds: 16,18,20…”
Section: A C K N O W L E D G E M E N T Smentioning
confidence: 99%
“…13 Hussen and colleagues 10 suggested that patient attendance at a first visit, or even a second visit, does not necessarily suggest long-term engagement, because only 50-89% of young people with HIV who successfully transition were retained in adult care after 1 year, and even fewer (56%) after 2 years. 17,48 This poor retention suggests transfer is an important but insufficient piece of health-care transition-akin to care linkage after a positive HIV test result being crucial to, yet unique from, care engagement. 49 The development of a system such as a patient registry, like the one available in some European countries, 28,29,50,51 would allow young people with HIV to be clinically followed up, and the completion and outcome of the health-care transition process documented.…”
Section: Evaluation Of Health-care Transitionmentioning
confidence: 99%